VD_FINDINFO Décision / 2015 / 15 vom 26. November 2014 - VD Tribunal cantonal (2014)
CLASSEMENT DE LA PROCÉDURE, FRAIS DE LA PROCÉDURE, INDEMNITÉEN GÉNÉRAL, PRÉVENU | 319 CPP (CH), 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH), 430 CPP (CH)